(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pharmaceutical nanotechnology is the instigative, fleetly arising branch of medical wisdom that deals with employing nanoscale accoutrements as medicine delivery and/ or individual tools. As medicine delivery tools, nano- delivery systems can be used to enhance the point-specific, targeted delivery of precise drugs. Artificial intelligence(AI) and nanotechnology are two several fields that are necessary in realizing the thing of perfection drug acclimatizing the stylish treatment for each cancer case. Recent conversion between these two fields is enabling better case data accession and bettered design of nanomaterials for perfection cancer drug. Individual nanomaterials are used to assemble a case-specific complaint profile, which is also abused, through a set of remedial nanotechnologies, to ameliorate the treatment outgrowth. Still, high intratumor and interpatient heterogeneousness make the rational design of individual and remedial platforms, and analysis of their affair, extremely delicate. Integration of AI approaches can bridge this gap, using pattern analysis and bracket algorithms for bettered individual and remedial delicacy. Nanomedicine design also benefits from the operation of AI, by optimizing material parcels according to prognosticated relations with the target medicine, natural fluids, vulnerable system, vasculature, and cell membranes, all affecting remedial efficacy. Then, abecedarian generalities in AI are described and the benefactions and pledge of nanotechnology coupled with AI to the future of perfection cancer drug are reviewed.